Long noncoding RNAs as therapeutic targets to overcome chemoresistance in ovarian cancer - Chen, Linjiao; Wang, Jie; Liu, Qian (Frontiers in Cell and Developmental Biology, 2022)
Long noncoding RNAs (lncRNAs) have been characterized to play an essential role in ovarian tumorigenesis via controlling a variety of cellular processes, such as cell proliferation, invasion, apoptotic death, metastasis, cell cycle, migration, metabolism, immune evasion, and chemoresistance. The one obstacle for the therapeutic efficacy is due to the development of drug resistance in ovarian cancer patients. Therefore, in this review article, we describe the role of lncRNAs in chemoresistance in ovarian cancer. Moreover, we discuss the molecular mechanism of lncRNAs-involved drug resistance in ovarian cancer. We conclude that lncRNAs could be useful targets to overcome chemoresistance and improve therapeutic outcome in ovarian cancer patients.